2-ketoglutarate dehydrogenase deficiency with intermittent 2-ketoglutaric aciduria - Dunckelmann, Robert; Ebinger, Friedrich; Schulze, Andreas; Wanders, R. J. A.; Rating, Dietz; Mayatepek, Ertan (Neuropediatrics, 2000)
Thieme E-Books & E-Journals
Gesehen am 18.01.2021